Prevalence and Association of Helicobacter pylori Infection in Gastric Disease at Dr. Cipto Mangunkusumo General National Hospital 2010–2021 - Simadibrata, Marcellus; Mustikarani, Dewi (The Indonesian Society for Digestive Endoscopy, 2023)
Background: Several studies showed contrasting associations between Helicobacter pylori infection and organic gastric disorders. We aim to determine the association between H. pylori infection and gastroesophageal reflux disease (GERD), gastric polyp, and gastric cancer in an Indonesian national referral hospital.Method: Data collected from patients referred to Cipto Mangunkusumo General National Hospital, Jakarta, Indonesia, from 2010 to 2021, with complete H. pylori test and endoscopy from electronic medical record. Chi-square analysis and logistic regression were performed to determine the association with a significant p-value of 0.05.Results: Three hundred and fourteen consecutive patients were enrolled, with a median age of 51.0 (16‒85), and 131 (41.7%) of them were males. The prevalence of H. pylori infection in organic gastric disease was 7.6% (n = 24) with 0.3% (n = 1) of them has gastric cancer, 3.2% gastric polyp (n = 10), and 4.1% (n = 13) GERD. A proven association between H. pylori infection and GERD was observed (RR = 26.42; 95% CI: 76.12‒114.05; p = 0.000) and esophagitis (RR = 2.44; 95% CI: 1.71‒3.49; p = 0.000). However, no significant association was found between H. pylori infection and gastric cancer (RR = 4.07; 95% CI: 0.26‒64.09; p = 0.28), and gastric polyp (RR = 1.16; 95% CI: 0.61‒2.22; p = 0.65).Conclusion: Our study suggested association of H. pylori infection in GERD and oesophagitis patients. Insignificant association was observed between H. pylori infection and gastric cancer, and gastric polyp.Keywords: Helicobacter pylori, esophagitis, GERD, gastric polyps, gastric cancer